Optimizing Retail Excellence: Exploring The Dynamic Nexus Of Skills, Leadership, And Motivation In Enhancing Performance Among Luwes Purwodadi Supermarket Employees - Oxzy Yoga Pratama; Nurchayati Nurchayati; Suparmi Suparmi; Hasyim Hasyim (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research aims to determine the influence of ability and leadership on the performance of self-service employees through work motivation as an intervening variable at the Luwes Purwodadi Supermarket. The population is 150 employees with a sample of 109 respondents. Data collection methods used questionnaires and primary data, analyzed using SPSS 25 and multiple linear regression analysis. The research results show that ability has a positive and significant effect on employee performance, meaning that increasing ability can improve performance. Leadership also has a positive and significant effect on performance, emphasizing the role of leaders in creating a productive work environment. Work motivation has a positive and significant influence on employee performance, this shows that efforts to increase motivation can increase productivity. This research provides an understanding of the complex relationship between ability, leadership, work motivation, and performance in supermarkets. Companies can use these findings to develop more effective human resource management strategies. In conclusion, this research provides insights for human resource management and confirms the importance of capability development, effective leadership, and work motivation to achieve performance excellence in the self-service sector